Comparison of Fatty Acid Composition between Female and Male Japanese Quail Meats - Gecgel, Umit; Yilmaz, Ismail; Gurcan, Eser Kemal; Karasu, Salih; Dulger, Gizem Cagla (HINDAWI LTD, 2015)
The objective of the present study was to compare the proximate analysis, fatty acids composition, omega fatty acids, trans fatty acids (TFAs), and ratio of the total poly unsaturated fatty acid (Sigma PUFA) and total saturated fatty acid (Sigma SFA) of female and male quail meats. Significant differences were not observed between pH, crude fat, moisture, and ash content of female and male quail meats (p > 0.05). The male quail meat had higher fat and ash contents and lower moisture content than those of the female quail meat. The pHs of male and female quail meat were found to be 6.22 and 6.21, respectively. The results of the fatty acid composition analysis showed that C18:1 (42.14-41.23%), C16:0 (24.31-25.76%), C18:2 (13.82-13.42%), and C18:0 (7.49-7.32%) were found as the major fatty acids in the female and male quail meats. Total TFAs, Sigma SFA, monounsaturated fatty acids (Sigma MUFA), and Sigma PUFA content of the female and male quail meats were found to be 2.79-2.82%, 33.22-34.65%, 49.70-48.72%, and 14.29-13.81%, respectively.
Keywords: CONJUGATED LINOLEIC-ACID; QUALITY CHARACTERISTICS; NUTRITIONAL-VALUE; ISOMERS; RISK; Chemistry